Non-singular terminal sliding mode control of converter-fed DC motor system with mismatched disturbance compensation. (27th June 2022) - Rauf, Arshad; Zafran, Muhammad; Khan, Muhammad Sadiq Ali; Khan, Awais; Shah, Syed Awais Ali
In this paper, the problem of angular velocity trajectory tracking for converter-fed DC motor system with disturbances/uncertainties is addressed. The combination power converters with DC motors for generating 'smooth start of drives' has numerous practical applications. Achieving high performance in such systems is however limited by the influence of multiple disturbances. Furthermore, the conventional mathematical model complicates the ability to compensate the multiple disturbances. In this paper, a control structure with non-singular terminal sliding mode controller and a finite-time disturbance observer is proposed. First, a special state transformation is applied, aggregating disturbances/uncertainties in a sole perturbing term of the system expressed in new coordinates. Then, the observer estimates the information about the lumped disturbances and the obtained estimated signals are used to construct a sliding surface. Finally, the sliding mode controller is applied to achieve desired result. The efficiency of the proposed control method is validated through numerical simulations.